Kepemilikan Institusional, Manajemen Laba dan Leverage Terhadap Kinerja Perusahaan - Maryati Rahayu; Bida Sari (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
The purpose of this study was to determine the influence of Institutional ownership, Management profit and leverage to the company performance by taking samples to manufacturing companies who registered at the indonesian stock exchange the period 2012 - 2015 as many as 19 company with the sample collection in purposive sampling .Data processed using spss.20. Based on sample t test known Institutional ownershipand Managementprofitwill not affect to the company performance in the proxy with cash flow return on asset, only leverage in the proxy with debt to equity ratio that influence the company performance.Based on ANOVA test, there is influence between institutional ownershi,Managementprofitand debt to equity ratio to the company performance simultaneously. The value of the determination adjusted r square of 15,5 %. While the rest 84,5 % can be explained by other factors that is not incorporated into research.